The microbiological quality of raw milk after introducing the two day's milk collecting system - Godič Torkar, Karmen (Acta agriculturae Slovenica, 2008)
This study was carried out to investigate the quality of raw milk after the decision of the dairies to collect the milk every two days and not daily as it has been performed till the year 2005. In wider central Slovenian production area we collected in winter and summer season 203 raw milk samples obtained from farm bulk milk tanks, collecting points and transportation tanks at the entrance to the dairy was studied. The total bacterial count, the number of coliforms, psychrotrophic micro-organisms, coagulase-positive staphylococci, yeasts and moulds were analysed using standard methods. The presence of mould species and production of aflatoxins were studied as well. The total bacterial count was higher than 100 000 cfu/ml in 48 (23.6%) out of all tested samples. Its mean value in all milk samples was 4.5 log10 cfu/ml . The mean numbers of coliform bacteria, psychrotrophic micro-organisms, yeasts and moulds together, and coagulase-positive staphzlococci were 2.1 log10 cfu/ml, 3.7 log10 cfu/ml, 2.3 log10 cfu/ml and 1.97 log10 cfu/ml, respectively. The yeasts were present in 95.0% of raw milk samples with the mean concentration of 1.7 log10 cfu/ml. Moulds were found in 63.3% of raw milk samples, their mean concentration was 0.6 log10 cfu/ml. Isolated mould strains belonged to genera Geotrichum (51.5%), Aspergillus (33.8%), Mucor (5.9%), Fusarium (2.9%) and Penicillium (2.9%). None of the isolated Aspergillus strains with typical growth on AFPA medium produced aflatoxin M1 on YES or YZGC medium supplemented with Methyl-ß-cyclodextrin.
Keywords: mleko; surovo mleko; mikrobiološka kakovost; mikroorganizmi; plesni